The impact of phenotypic appearance on body weight and egg production in laying hens: A group-size- and experience-dependent phenomenon - Marin, Raul Hector (2014)
Alterations of birds' phenotypic appearance (PA) may lead to unwanted behaviors, potentially impairing poultry welfare, health, and productive performance. Likewise, group size may play an important role modulating the expression of adaptive behaviors. This study evaluates whether changes in the PA of Hyline Brown laying hens may affect their BW and egg production, and if so, whether these effects depend on group size. A total of 1,050 one-day-old chicks were randomly assigned to 1 of 45 pens. Groups were of 10, 20, or 40 individuals (8 hens/m2). At arrival, the PA of 0, 30, 50, 70, or 100% of the birds within each group was artificially altered by marking the back of their heads black. The remaining birds within groups were unaltered. The 30% marked hens within groups of 10 individuals had a lower BW at 24 wk of age than their 70% unmarked counterparts, whereas the other groups showed similar BW. No differences were detected in egg laying performance during this phase. Next, within the initially homogeneous groups (0 and 100%), 30, 50, and 70% of the hens were either marked or unmarked (PA changed) sequentially at 34, 38, and 44 wk of age. Hens within the initially heterogeneous groups of 30, 50, and 70% marked birds remained unchanged and were used as controls. Groups of 40 individuals showed a reduction in BW gain and weekly hen-day-egg production after 30% PA changes, as compared with control counterparts. No differences were found in pens of 10 hens, and the groups of 20 showed intermediate results. A transient reduction in egg production was found after 50% PA changes. No further productive effects were observed after 70% changes. Our findings suggest that differences in hen appearance, which may occur due to variations in health status, injuries, and other natural causes, can be critical for production and welfare management practices depending both on the flock size and the birds' previous experience in exposure to group phenotypic heterogeneity. © 2014 Poultry Science Association Inc.